Diseño de modelo de valoración de las políticas contables de labs transportes de carga S.A.S. (2020)
This researching aims through the development of the specific objectives to solve the problem of the Enterprise Labs high load carrying S.A.S located in Duitama City and to know if through the countables and financiers politics can be upgraded the internal inspection with the designing of an assessment model of the those. It’s propose to use a descriptive and explanatory researching with a qualitative approach. To the collection of the information, mainly we based on enterprises documents and an in a poll made by partners of that and it’s concluded the importance of the regular review of the countables politics and the socialization with its employers especially of the accounting area, the proposed upgrades to some chosen politics are closed related to the internal inspection and these let the normal development of the activities and they will be a guide or supporting that must be inside the organization.